Influencing Social Inclusion and Exclusion of Students from Socially and Economically Weaker Sections of Society in a Private School - Role of School Leadership and other Actors - Singh Deepika K (International Journal for Transformative Research)
The paper is based on a qualitative study of a private school based in Ahmedabad, India. The research aimed to understand the practicalities of social inclusion. I argue ‘inclusion’ and ‘exclusion’ are processes and not a condition of being or an event. These processes unfold every moment through interaction of learners and other stakeholders in school. The interaction amongst a particular set of stakeholders is also different in different contexts. The presence and absence of a particular stakeholder/power/position holder influences the interaction. The larger policies are interpreted at multiple levels and converted into systems, processes and structures which further are expected to exhibit certain mindset and behaviour by the key actors. However, the key actors’ behaviour is influenced by presence and absence of ‘others’ who are perceived with power.